Growth and yield of fennel (Foeniculum vulgare Mill.) as influenced by irrigation, nutrient levels and crop geometry - O P Aishwath, R S Mehta, M M Anwer, (Journal of Spices and Aromatic Crops, 2011)
A field experiment was conducted during 2003-06 at Ajmer (Rajasthan) to study the growth, profitability and productivity of fennel (Foeniculum vulgare) as influenced by irrigation (12, 15 and 18 days interval), nutrients levels (N and P2O5 each at 60/30, 90/40 and 120/50 kg ha-1) and crop geometry (40 cm x 25 cm, 50 cm x 25 cm and 60 cm x 25 cm). Significantly higher yield attributes, seed yield and N, P and K uptake was obtained with 15 days irrigation interval. Growth parameters, yield attributes, yield and N, P and K uptake were significantly higher with application of 120 kg N and 50 kg P2O5 ha-1. Crop geometry of 60 cm x 25 cm resulted in significantly higher seed yield. Thus, irrigation at 15 days interval with 120 kg N and 50 kg P2 O5 ha-1 at 60 cm x 25 cm was optimum for realizing higher yield, profitability and productivity of fennel.